China, Japan and the East China Sea Imbroglio. (3rd July 2017) - Jash, Amrita
ABSTRACT: The East China Sea dispute has become a characteristic feature in the defined "hot economics, cold politics" relations between China and Japan. The maritime sphere has gained precedence in the larger realm of diplomacy, thus making the contested waters a primary hotspot of power politics between the two Asian countries. With the growing tensions, in all likelihood the maritime dispute will be high on the political and security agenda of China and Japan. What makes this worrisome is that the dispute does not just make the bilateral relations unstable but holds significant implications for East Asia's regional stability. In this regard, given the phenomenon of constant testing of each other's resolve, the possibility of an all-out confrontation in the East China Sea remains a vital concern. What has further added to the power struggle is the US involvement, thus making the dispute a difficult case to resolve. The crux of the paper lies in understanding the volatility of the East China Sea dispute between China and Japan. In doing so, the paper examines the determinants of the dispute, the actors involved and their responses.